2016
DOI: 10.7759/cureus.705
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Planning Considerations for Robotic Guided Cardiac Radiosurgery for Atrial Fibrillation

Abstract: PurposeRobotic guided stereotactic radiosurgery has recently been investigated for the treatment of atrial fibrillation (AF). Before moving into human treatments, multiple implications for treatment planning given a potential target tracking approach have to be considered.   Materials & MethodsTheoretical AF radiosurgery treatment plans for twenty-four patients were generated for baseline comparison. Eighteen patients were investigated under ideal tracking conditions, twelve patients under regional dose rate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 61 publications
2
47
0
Order By: Relevance
“…Finally, we added initial technical, pre-clinical, and clinical manuscripts not covered by the search based on our own experience in cardiac radiosurgery in the past 12 years. Evidence was finally extracted from the remaining 42 manuscripts, which include reports on two clinical trials [22,23], two clinical case series [24,25], eight case reports [19,20,[26][27][28][29][30][31], eight preclinical studies [18,[32][33][34][35][36][37][38][39], fourteen technical studies [40][41][42][43][44][45][46][47][48][49][50][51][52][53], and eight reviews or opinions [7,[54][55][56][57][58][59][60].…”
Section: Clinical Trial and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we added initial technical, pre-clinical, and clinical manuscripts not covered by the search based on our own experience in cardiac radiosurgery in the past 12 years. Evidence was finally extracted from the remaining 42 manuscripts, which include reports on two clinical trials [22,23], two clinical case series [24,25], eight case reports [19,20,[26][27][28][29][30][31], eight preclinical studies [18,[32][33][34][35][36][37][38][39], fourteen technical studies [40][41][42][43][44][45][46][47][48][49][50][51][52][53], and eight reviews or opinions [7,[54][55][56][57][58][59][60].…”
Section: Clinical Trial and Literature Reviewmentioning
confidence: 99%
“…There are already various studies published for catheter ablation which investigated the cardiac and respiratory motion of cardiac substructures to obtain a better registration between electrophysiological measurements and pre-procedural imaging [61]. Additionally, for RA/CRS, two studies investigated the motion of the left atrium and the pulmonary veins, and found highly variable respiratory and cardiac motion ranges and also differential motion between left, right, anterior, and posterior pulmonary veins [45,47]. However, with most modern radiotherapy equipment, the major source of motion (namely originating from respiration) can be compensated to a high degree of accuracy [62], while cardiac contraction motion seems to have a limited impact on the dose distribution [53].…”
Section: Technical Studies For Cardiac Radiosurgerymentioning
confidence: 99%
“…For AF treatment plans, margin sizes less than 3-5 mm may be within acceptable limits [12], [33]. Therefore, the tracking error of the tracking algorithm in our study (3.7 ± 0.6 mm) could contribute to the proof-of-concept for non-invasive cardiac radiosurgery under real-time MRI guidance.…”
Section: Discussionmentioning
confidence: 60%
“…Although not detailed in this work, we expect that this validation method could be used for a range of tracking validations and treatment planning studies, especially when 4D patient data is difficult to acquire. In fact, imaging data comprising cardiac and respiratory motion alike would have been helpful in previous treatment planning studies for cardiac radiosurgery [12,33]. The analysis in this work was made possible by validation through quantitative measures provided by the XCAT digital phantom for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…A study recently analyzed treatment planning for pulmonary vein isolation using CyberKnife in patients with atrial fibrillation and showed that CyberKnife could be used in up to 40% of patients for atrial fibrillation ablation. It is thought that with improved motion‐tracking systems and SRS technology, a larger percentage of patients can be eligible for the procedure.…”
Section: Discussionmentioning
confidence: 99%